Pemberdayaan Pelaku Usaha Konveksi Berbasis Rumah di Jurangmangu Tentang Pengelolaan Keuangan untuk Meningkatkan Kesejahteraan - Ratnaningtyas, Heny; Sugeng, Novita Widyastuti; Nurbaeti, Nurbaeti; Gantina, Devita (LPPM Universitas Bumigora, 2025)
Financial management counseling for home-based convection business actors in Jurangmangu, South Tangerang, was held to overcome the low understanding of working capital management, financial planning and risk mitigation. The aim of this activity is to increase participants' financial literacy so they can manage their businesses more effectively. The methods used include conveying participants' needs, compiling material, providing direct counseling, interactive discussions, and evaluation through pre-tests and post-tests. Post-evaluation results showed a significant increase in participants' understanding, with 100% answering correctly on the post-test counseling, compared to only 10-20% correct on the pre-test. The conclusion of this activity emphasizes the importance of good working capital management and financial planning to maintain business liquidity and stability. It is recommended that business actors continue to attend training and build good relationships with customers and suppliers to support the growth and desires of their business. Through the application of the knowledge gained, it is hoped that business actors can increase operational efficiency and achieve success in their business convection.